SHELLQs-JWST perspective on the intrinsic mass relation between supermassive black holes and their host galaxies at z > 6 - Silverman, John; Li, Junyao; Ding, Xuheng; Onoue, Masafusa; Strauss, Michael A.; Matsuoka, Yoshiki; Izumi, Takuma; Jahnke, Knud; Treu, Tommaso; Volonteri, Marta; Phillips, Camryn L.; Andika, Irham T.; et al. (The astrophysical journal. Part 2, Letters, 2025)
The relation between the masses of supermassive black holes (SMBHs) and their host galaxies encodes information on their mode of growth, especially at the earliest epochs. The James Webb Space Telescope (JWST) has opened such investigations by detecting the host galaxies of active galactic nuclei (AGN) and more luminous quasars within the first billion years of the Universe (z ≳ 6). Here, we evaluate the relation between the mass of SMBHs and the total stellar mass of their host galaxies using a sample of nine quasars at 6.18 ≤ z ≤ 6.4 from the Subaru High-z Exploration of Low-luminosity Quasars survey with NIRCam and NIRSpec observations. We find that the observed location of these quasars in the SMBH-galaxy mass plane (-9; -11) is consistent with a nonevolving intrinsic mass relation with dispersion ( dex) higher than the local value (∼0.3-0.4 dex) of their more massive descendants. Our analysis is based on a forward model of systematics and includes a consideration of the impact of selection effects and measurement uncertainties with an assumption on the slope of the mass relation. While degeneracies between parameters persist, the best-fit solution has a reasonable AGN fraction (2.3%) of galaxies at z ∼ 6 with an actively growing UV-unobscured black hole. In particular, models with a substantially higher normalisation in MBH would require an unrealistically low intrinsic dispersion (∼0.22 dex). Consequently, our results predict a large population of AGN at lower black hole masses, as are now just starting to be discovered in focused efforts with JWST.